The Effect of Marketing Mix, Hospital Image, and Patient Loyalty on Intention for Retreatment over Outpatient Care at Pasar Minggu Hospital during COVID-19 Outbreak - Sri kurnia wati; Sandra dewi; Rokiah Kusumapradja (Penerbit Kemala Indonesia, 2020)
The COVID-19 pandemic that has plagued Indonesia has affected the number of outpatient visits at Pasar Minggu Hospital. The several problems were found when the preliminary observations have been made. Here, the problems related to policies and regulations from the government and hospitals as well as patient complaints towards the services at the hospital. Thus, this study aimed to determine the effect of marketing mix, the hospital image, and patient loyalty on the patients' intention of returning for outpatient care. This research was an associative quantitative research through hypothesis testing. The study population was patients who were treated in an outpatient care. The method used in data analysis was multiple linear regressions. Here, the regression coefficient value obtained showed that the patient loyalty regression coefficient (0.288) had the highest value compared to the marketing mix coefficient (0.052) and hospital image (0.191). These results indicated the effect of patient loyalty to the hospital is very high so that it is reliable. In addition, patient loyalty also has most affected the patients' intention for retreatment in outpatient care. Simultaneously and partially, the results of data analysis and hypothesis testing proved that there was a positive and significant effect between the marketing mix, the hospital image, and patient loyalty on the patients' intention of returning for outpatient care at Pasar Minggu Hospital during Covid-19 pandemic.